Improved direct anonymous attestation scheme for mobile computing platforms - Li YANG; Jun-wei ZHANG; Jian-feng MA; Zhi-hong LIU (Tongxin xuebao, 2013)
The security flaws of a direct anonymous attestation scheme proposed by Ge,et al.Were analyzed,and the re-sult shows that the authentication protocol of the scheme is vulnerable to reply attacks and platform masquerade attacks when being used for remote attestation.An improved direct anonymous attestation authentication scheme with the in-volvement of key agreement was proposed to provide the property of mutual authentication.The analysis shows that the proposal can realize direct anonymous attestation with the properties of forgery-resistance and anonymity,and resist reply attacks and platform masquerade attacks; the scheme is effective and suitable for the mobile trusted computing platforms.